Neuroinflammation in Alzheimer's disease. Issue 4 (April 2015) - Heneka, Michael T; Carson, Monica J; Khoury, Joseph El; Landreth, Gary E; Brosseron, Frederic; Feinstein, Douglas L; Jacobs, Andreas H; Wyss-Coray, Tony; Vitorica, Javier; Ransohoff, Richard M; Herrup, Karl; Frautschy, Sally A; et al.
Summary: Increasing evidence suggests that Alzheimer's disease pathogenesis is not restricted to the neuronal compartment, but includes strong interactions with immunological mechanisms in the brain. Misfolded and aggregated proteins bind to pattern recognition receptors on microglia and astroglia, and trigger an innate immune response characterised by release of inflammatory mediators, which contribute to disease progression and severity. Genome-wide analysis suggests that several genes that increase the risk for sporadic Alzheimer's disease encode factors that regulate glial clearance of misfolded proteins and the inflammatory reaction. External factors, including systemic inflammation and obesity, are likely to interfere with immunological processes of the brain and further promote disease progression. Modulation of risk factors and targeting of these immune mechanisms could lead to future therapeutic or preventive strategies for Alzheimer's disease.